PELAKSANAAN PROMOSI TAMAN MARGASATWA KASANG KULIM KABUPATEN KAMPAR PROVINSI RIAU - Yashinta Wulandari; Firdaus Yusrizal (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
The purpose of this research is to know the promotion mix of tourism object and visitor's responds about the promotion mix which had performed by Taman Margasatwa Kasang Kulim's management. The samples on this research are 100 people, who were taken by using accidental sampling. Based on the both of goals to be achieved, this research used descriptive qualitative technique with triangulation method as the testing of the data validity and descriptive quantitative technique with percentage method as the result statements of visitors‟s respond. The results of this research are Taman Margasatwa Kasang Kulim's management has performed the promotional mix in the form of advertising through newspapers and billboard, personal selling, sales promotion, and public relations. Based on the visitors's respond, the ability of the newspaper as a media promotion through advertising has been accomplished amounting to 67,4%, the billboard amounting to 69,3%, sales promotion amounting to 71,5%, and public relations amounting to 80,1%. Overall, the promotion implementation of Taman Margasatwa Kasang Kulim, Kampar regency, Riau province has been accomplished amounting to 71,2%.Keywords: Advertising, Personal Selling, Sales Promotion, Public Relation